Multidrug-resistant ST11-KL64 hypervirulent Klebsiella pneumoniae with multiple bla- genes isolated from children's blood - Luo, Rongmu; Ma, Guannan; Yu, Qian; Tian, Zhengqin; Man, Qihang; Shu, Xiangrong; Liu, Xuetong; Shi, Yupeng; Zhang, Lei; Wang, Jingbo (Frontiers in Pediatrics, 2025)
IntroductionHypervirulent carbapenem-resistant Klebsiella pneumoniae (hv-CRKP) poses an increasing public health risk due to its high treatment difficulty and associated mortality, especially in bone marrow transplant (BMT) patients. The emergence of strains with multiple resistance mechanisms further complicates the management of these infections.MethodsWe isolated and characterized a novel ST11-KL64 hv-CRKP strain from a pediatric bone marrow transplantation patient. Antimicrobial susceptibility testing was performed to determine resistance patterns. Comprehensive genomic analysis was conducted to identify plasmid types, virulence factors, and antimicrobial resistance genes, as well as potential resistance mechanisms associated with mutations and plasmid-mediated variants.ResultsThe isolated hv-CRKP strain exhibited multidrug resistance to carbapenem, tigecycline, and polymyxin. Genomic analysis revealed that the IncHI1B/repB plasmid carried virulence factors (rmpA, ΔrmpA2, iucABCD, iutA), while IncFII/IncR and IncFII plasmids harbored resistance genes [blaCTX-M-65, blaTEM-1B, rmtB, blaSHV-12, blaKPC-2, qnrS1, blaLAP-2, sul2, dfrA14, tet(A), tet(R)]. The coexistence of blaCTX-M-65, blaTEM-1B, blaSHV-12, blaLAP-2,and blaKPC-2 in one hv-CRKP strain is exceptionally rare. Additionally, the Tet(A)-S251A variant in the conjugative plasmid pTET-4 may confer tigecycline resistance. Mutations in MgrB, PhoPQ, and PmrABCDK were identified as potential contributors to increased polymyxin resistance. Interestingly, plasmid-encoded restriction-modification systems and Retron regions were identified, which could potentially confer phage resistance.DiscussionThe combination of virulence and antimicrobial resistance factors in the ST11-KL64 hv-CRKP strain represents a significant challenge for treating immunocompromised pediatric patients. Particularly concerning is the resistance to polymyxin and tigecycline, which are often last-resort treatments for multidrug-resistant infections. The findings highlight the urgent need for effective surveillance, infection control measures, and novel therapeutic strategies to manage such hypervirulent and multidrug-resistant pathogens.